Thymic amyloidoma mimicking sclerosing thymoma in a triple vessel disease patient: An incidental finding - Harshi Dhingra; Amarjit Singh; Asif Baliyan; Vinisha Bansal (Wolters Kluwer Medknow Publications, 2020)
A 65 year old man who underwent coronary artery bypass graft (CABG) for triple vessel disease was found to have enlarged thymus. Biopsy of the thymic mass revealed localised amyloid deposits demonstrating strong apple green birefringence on polarised microscopy. Localized thymic amyloidosis is an extremely rare finding with present case as the seventh in the world and the first in India. Review of literature of thymic amyloidoma and its close differential sclerosing thymoma is hereby described.